2009
DOI: 10.1002/qua.22136
|View full text |Cite
|
Sign up to set email alerts
|

NMR spin–spin coupling constants and hyperconjugative interactions

Abstract: ABSTRACT:The potential of NMR spin-spin coupling constants as probes to study fine details of electronic molecular structures is briefly discussed in this work through two different examples. A qualitative analysis of the polarization propagator expression for the Fermi contact term is applied for predicting factors affecting 1 J CH , and comments are made about how to generalize those results to different types of onebond spin-spin couplings. Moreover, the Natural J Coupling method is applied to get insight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…σ→σ*, σ→π*, nx→σ*, nx→π*, hyperconjugation, and homohyperconjugative interactions significantly affect the Fermi contact contribution to the scalar spin–spin coupling constant. Therefore, the C–H coupling constants were used to investigate the stereoelectronic effects [ 64 – 65 ]. The main interactions found by NBO are listed in Supporting Information File 1 .…”
Section: Resultsmentioning
confidence: 99%
“…σ→σ*, σ→π*, nx→σ*, nx→π*, hyperconjugation, and homohyperconjugative interactions significantly affect the Fermi contact contribution to the scalar spin–spin coupling constant. Therefore, the C–H coupling constants were used to investigate the stereoelectronic effects [ 64 – 65 ]. The main interactions found by NBO are listed in Supporting Information File 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This fact has been recently interpreted as a consequence of hyperconjugative interactions between orbitals of the coupling pathway and those of carbonyl group. 8,23,24 It is also noteworthy that the value of coefficient S 2 is larger than those of S 1 and C 3 (extra coefficient regarding classic Karplus equation) suggesting a more important role in the fitting of truncated Fourier series.…”
mentioning
confidence: 96%
“…B3LYP/TZVP level of theory has proved to provide similar results to those of ab initio SOPPA and SOPPA(CCSD) methods with larger basis sets 19 and has been used successfully in the calculations of J and hyperfine couplings. [20][21][22][23][24] (5) The nine sets of coupling constants 3 J XY and the angles from geometry optimizations were used to calculate the six corresponding Fourier coefficients in Eq. (1), solving 6 × 6 system of nonhomogeneous linear equations.…”
mentioning
confidence: 99%
“…The authors found a relevant contribution from the S 2 term and rather unexpected positive C 1 coefficient. The latter has been interpreted in terms of hyperconjugative interactions [98,100,101].…”
mentioning
confidence: 99%
“…In this sense, exploring the dependence of a given J-coupling over the entire range of values of the corresponding dihedral angle can be better achieved using ab initio calculations [24,80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]107,[111][112][113][114][115][116][117][118][119][120][121][122][123]. Whether or not the associated Karplus fit will improve over the empirical ones for structure determination critically depends on the ability of the computational model (i.e.…”
mentioning
confidence: 99%